Creating the Situation of Success as Implementation of the Optimism Idea: Pedagogic Interpretation of M. Seligman’s Theory - ￼Y. V. Andreyeva (Образование и наука)
The paper is devoted to the Optimism Theory by Martin Seligman that can be used for creating the model of positive emotional response aimed at improving the effectiveness of educational process. The author shares the idea of the contemporary American psychologist and philosopher regarding the optimism as the acquired skill affecting the students’ academic progress, and recommends developing students’ self-assurance by addressing a situation of success. Such situation is considered as both the leading factor and pedagogic condition, and the technological base for promoting personal optimism.The educational significance of success is based on its ability to change students’ attitude as the result of personal achievements. The lack of motivation, as the main teaching problem, can be overcome by assisting students in their academic progress and addressing the situation of success. The pedagogic techniques improving motivation to overcome learning difficulties on the way to success are given providing adolescents with effective assistance and emotional support. According to the author, the situation of success is not a temporary pedagogic tool, but rather a way of achieving optimistic outlook, which allows students themselves to solve complex learning tasks and achieve desired results without pedagogic facilitation.